2021
DOI: 10.3390/plants10102098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Host on the Primary Metabolic Profiling of Cuscuta Campestris’ Main Organs, Haustoria, Stem and Flower

Abstract: Cuscuta campestris (dodder) is a stem holoparasitic plant without leaves or roots that parasitizes various types of host plants and causes damage to certain crops worldwide. This study aimed at gaining more knowledge about the effect of the hosts on the parasite’s levels of primary metabolites. To this end, metabolic profiling analyses were performed on the parasite’s three main organs, haustoria, stem and flowers, which developed on three hosts, Heliotropium hirsutissimum, Polygonum equisetiforme and Amaranth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, increased levels in phenylpropanoids such as coumaric acid, 2,5-dihydroxybenzoate, ferulic acid, and shikimate were also observed in our study. In another recent study, where metabolic profiling analyses were performed on the parasite’s three main organs, haustoria, stem, and flowers, developing on three different hosts ( Heliotropium hirsutissimum, Polygonum equisetiforme, and Amaranthus viridis ) revealed that the metabolic profile of C. campestris parasitising different host species was characterised by noteworthy differences, suggesting that the parasites significantly rely on the host’s metabolites and that the parasite is able to self-regulate its metabolism (Kumar and Amir 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, increased levels in phenylpropanoids such as coumaric acid, 2,5-dihydroxybenzoate, ferulic acid, and shikimate were also observed in our study. In another recent study, where metabolic profiling analyses were performed on the parasite’s three main organs, haustoria, stem, and flowers, developing on three different hosts ( Heliotropium hirsutissimum, Polygonum equisetiforme, and Amaranthus viridis ) revealed that the metabolic profile of C. campestris parasitising different host species was characterised by noteworthy differences, suggesting that the parasites significantly rely on the host’s metabolites and that the parasite is able to self-regulate its metabolism (Kumar and Amir 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol to determine the primary metabolites is based on our previous studies [12,15,[18][19][20]. Each of the broomrape samples was homogenized using a Restch MM 301 homogenizer.…”
Section: Extraction Of Primary Metabolites and Analysis Using Gas Chr...mentioning
confidence: 99%
“…Yet, many questions remain unanswered regarding the dependence of the parasite on the metabolites of their hosts [7]. Recently, in a study of the metabolic profiles of three main organs of the holoparasitic plant Cuscuta campestris (dodder) that developed on three different hosts, it was discovered that the levels of metabolites in the parasite differed significantly between the hosts [18]. This suggests that the parasites rely heavily on the host's metabolites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 11 papers were collected for the SI; of them, five original research papers present new strategies in parasitic weeds management [ 11 , 12 , 13 , 14 , 15 ], two focused on crop resistance to parasitic plants [ 16 , 17 ] and three provide new insights on plant—parasite interaction [ 18 , 19 , 20 ]. One Opinion Paper provides a personal view of the present status of parasitic weed problems and their control written by Chris Parker, who dedicated his entire long scientific career to parasitic plants and their management [ 21 ].…”
mentioning
confidence: 99%